THE IMPACT OF STRESS ON DECISION-MAKING AND PERFORMANCE IN ROCK CLIMBING: A LITERATURE REVIEW - Adam Borsuk; Martyna Narożniak; Julia Skowrońska-Borsuk; Adrianna Ewa Pękacka; Bartłomiej Czerwiec; Joanna Katarzyna Pergoł; Malwina Wojtas; Julia Borkowska; Zuzanna Krupa; Julia Sposób (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Sport climbing, as a high-risk activity, provides a valuable framework for analyzing the impact of stress on decision-making processes. This paper aims to explore specific aspects of climbing that may influence cognitive processes and, consequently, the behavior of individuals engaged in this demanding sport discipline. Material and methods: A thorough review of the literature available on PubMed and Google Scholar databases was conducted using following keywords: “rock climbing”, “lead climbing”, “top rope climbing”, “bouldering”, “stress”, “decision-making” Conclusions: Stress significantly affects climbers’ cognitive and physical performance, especially among less experienced individuals. However, psychological resilience, experience, and mental training can mitigate its negative impact. When properly managed, stress may even enhance performance and adaptability. Therefore, climbing training should include psychological preparation to improve decision-making, focus, and safety in high-risk conditions.